Immunogenic potential of biogenic vs. synthetic selenium nanoparticles in vaccine candidate against methicillin-resistant Staphylococcus aureus - Alireza Ranjbariyan; Setareh Haghighat; Mohammad Hossein Yazdi; Sepideh Arbabi Bidgoli; Hedieh Moradi Tabriz; Mehdi Mahdavi (Vaccine: X)
MRSA-related antimicrobial-resistant infections are a significant public health issue. Vaccination can prevent infection by inducing pathogen immunity. The surface-associated protein autolysin is a promising vaccination candidate. This study investigated the immunogenicity and MRSA protection of a recombinant R-autolysin vaccination with SeNPs and aluminum adjuvants. R-autolysin was expressed and purified using nickel-nitrilotriacetic acid affinity chromatography. Synthetic and biogenic SeNPs are prepared from selenium dioxide and Lactiplantibacillus plantarum. Dynamic light scattering and scanning electron microscopy assessed SeNP shape and size. Balb/c mice received three subcutaneous vaccination injections with aluminum adjuvants and SeNPs over two weeks. ELISA measured cytokines and antibodies to determine the immunological response. Opsonophagocytosis tests, internal organ bacterial load, and experimental group survival rates assessed the vaccine's efficacy. Additionally, pathobiological changes were compared among the groups to determine any differences in response. The study demonstrated that mice immunized with SeNPs and r-autolysin produced more IgG, IgG1, and IgG2a antibodies and cytokines, including IFN-γ, TNF, IL-12, and IL-4, than the control group. The immunized mice had higher survival rates and lower internal organ bacterial burdens than the control group. The results indicate that SeNPs and r-autolysin improved the immune response and protected against MRSA infection. Biogenically and synthetically generated SeNPs improve immune response and reduce mouse mortality. Notably, synthetic SeNPs stimulated humoral immunity more than biogenic SeNPs, which stimulated cellular immunity.